(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
The m? structure introduce pure and applied mathematics using the set FpZ = Fp ? xpZ | e(x ? 0(mod(p))), p prime, to then present mathematical structures resulting from the sets originally introduced F. Ayissi Eteme [6]. This work consists in defining on FpZ the notion of Ham- ming code according to m? set structure. We show a relation between m? protocol F5 and Hamming m? code. By using this relation, we get a new steganography based on the bit modalities of a code word.